Improved pregnancy outcome in refugees and migrants despite low literacy on the Thai-Burmese border: results of three cross-sectional surveys - De Pree Cecilia; Hogan Celia; Carrara Verena I; Nosten Francois; McGready Rose (BMC, 2011)
Abstract Background Maternal and infant health has been associated with maternal education level, which is highly associated with literacy. We aimed at estimating literacy rates among reproductive age women attending antenatal clinics in camps for refugees and in migrant clinics in Tak province, north-western Thailand, to determine whether illiteracy had an impact on birth outcomes. Methods Three reading assessments were conducted using an identical method each time, in 1995-97, 2003 and 2008. Midwives chose at random one of four pre-set sentences. Each woman was asked to read aloud and scoring was based on a "pass/fail" system. Pregnancy outcomes were compared with maternal literacy rate. Results Overall, 47% (1149/2424) of women were able to read. A significant improvement was observed among migrant (34% in 2003 vs. 46% in 2008, p = 0.01), but not refugee (47% in 1995-97, 49% in 2003, and 51% in 2008) women. Literate women were significantly more likely to be of non-Karen ethnicity, primigravidae, non-smokers, to remain free from malaria during pregnancy and to deliver in a health clinic. Significant improvements in pregnancy outcome (reductions in premature births, low birth weight newborns and neonatal death) between 1995-97 and 2003 were unrelated to literacy. Conclusions Significant reductions in poor pregnancy outcome over time have not been driven by changes in literacy rates, which have remained low. Access to early diagnosis and treatment of malaria in this population, and delivery with skilled birth attendants, despite ongoing low literacy, appears to have played a significant role.